EXPLORING PSYCHOSOCIAL FACTORS LINKING PERSONALITY DISORDERS TO QUALITY OF LIFE (Journal of Medical & Health Sciences Review, 2025)
Introduction: Personality disorders comprise a heterogeneous group of psychiatric conditions defined by enduring patterns of cognition, affect, and behavior that deviate substantially from societal norms, resulting in significant functional impairment or subjective distress. These disorders, including borderline, antisocial, and obsessive-compulsive personality disorders, are distinguished by distinct configurations of maladaptive personality traits. Objective: To examine the extent to which different types of personality disorders are associated with variations in quality of life across physical, psychological, social, and environmental domains. To identify and analyze the specific psychosocial factors, including coping mechanisms, self-esteem, social support, and cognitive distortions, that mediate the impact of personality disorders on quality of life. Method: The study recruited 12 individuals with personality disorders and 15 mental health professionals from clinical settings and support groups in Quetta, Pakistan. Results: Participants ranged in age from 26 to 52 years (M = 37.25, SD = 8.02) and had varied educational backgrounds: four held Bachelor's degrees, four Master's, three High School diplomas, one Doctorate, and one Associate's degree. Discussion: The study explored the complex relationship between personality disorders and quality of life, emphasizing the impact of psychosocial factors on individuals' overall well-being. Conclusion: This study contributes to the growing body of literature that emphasizes the interplay between personality disorders and quality of life.